Preparation method of 32P-loaded ultrathin flaky chitosan hydrogel applicator
By applying ultra-hydrophilic coating and light curing technology to the mold, an ultra-thin sheet chitosan hydrogel applicator was prepared, which solved the problem of blocking rays with excessive thickness of existing hydrogel applicators, achieving higher efficacy and ray penetration.
Patent Information
- Application Number
- CN202510046650.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing 32P-loaded hydrogel applicator is too thick, which hinders the spread of β-rays and affects the treatment effect.
An extremely thin hydrogel applicator is prepared by applying ultra-thin sheet chitosan hydrogel applicator to a mold by applying ultra-hydrophilic coating and light curing technology.
It reduces the blockage of the hydrogel material on rays, enhances the efficacy of the applicator, and reduces the solid content, further improving the penetration of rays.
Smart Images

Figure CN119792586A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomedical materials, specifically a load 32 Preparation method of ultrathin chitosan hydrogel applicator of P. Background Art
[0002] Isotope radiotherapy is an effective means of treating keloids in clinical practice. It uses the beta rays released by isotopes to bombard the DNA chains of the nuclear cells of the irradiated tissue, causing cell death and disintegration, thus achieving the therapeutic effect. This method has a low recurrence rate and can provide targeted treatment to the local area. Phosphorus 32 is a radioactive isotope of the element phosphorus, with the symbol 32 P. 32 P is the radioactive source of the applicator commonly used in hospitals. Its half-life is short, only two weeks. 32 The P applicator has the advantage of being customizable on-site according to the lesion site.
[0003] The Chinese patent application with publication number CN116196541A discloses a phosphorus isotope patch, in which a phosphorus isotope layer is arranged between a first base layer and a second base layer. The preparation of the phosphorus isotope layer includes multiple steps such as drawing a shape, cutting a pattern, calculating an area, first dropping of nuclides, first drying, second dropping of nuclides, and second drying. There are problems such as cumbersome and time-consuming process, waste of nuclides, and release of radioactive aerosols into the environment.
[0004] The Chinese patent application with publication number CN 116983464A discloses a load 32 The preparation method of the hydrogel applicator of P overcomes the problems existing in the preparation process of the phosphorus isotope layer. However, the hydrogel prepared by the preparation method is too thick. 32 The average range of the beta rays emitted by P in the tissue is 4 mm. Too thick a hydrogel will hinder the propagation of beta rays, thus affecting the therapeutic effect. Summary of the invention
[0005] The purpose of this application is a load 32 The invention discloses a method for preparing an ultra-thin sheet chitosan hydrogel applicator of P, and the invention can prepare an ultra-thin sheet chitosan hydrogel applicator.
[0006] This application provides a load 32 The preparation method of an ultra-thin sheet chitosan hydrogel applicator of P comprises:
[0007] (1) Add 1 g to 2 g of chitosan per 100 mL of water to prepare a chitosan aqueous solution;
[0008] (2) adding methacrylic anhydride dropwise to the chitosan aqueous solution to react to obtain methacrylic chitosan, wherein the molar ratio of methacrylic anhydride to amino groups in chitosan is 5-16:1;
[0009] (3) adding 400 mg to 500 mg of methacryloyl chitosan per 10 mL of water to prepare a methacryloyl chitosan aqueous solution;
[0010] (4) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacryloyl chitosan aqueous solution to obtain a chitosan hydrogel precursor solution, wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacryloyl chitosan is 1:8-20;
[0011] (5) coating the inner wall of the polytetrafluoroethylene mold with a super-hydrophilic coating and allowing it to air dry naturally;
[0012] (6) Na2H 32 PO4 aqueous solution and chitosan hydrogel precursor solution are added into the mold, stirred and then light-cured;
[0013] (7) The cured hydrogel is taken out and packaged between two layers of transparent tape to obtain an ultra-thin chitosan hydrogel applicator.
[0014] Furthermore, step (1) is specifically as follows: chitosan powder is added into water, and then acetic acid is added dropwise, and the mixture is placed in an oil bath at 60°C-70°C and stirred for 30min-60min until the chitosan powder is completely dissolved; the amount of acetic acid used is: the volume of acetic acid is 1%-2% of the volume of water.
[0015] Furthermore, step (2) is specifically as follows: methacrylic anhydride is added dropwise to the chitosan aqueous solution, and the mixture is reacted in a water bath at 55°C-65°C for 6h-8h, and then the reaction solution is adjusted to neutral, the neutral reaction solution is dialyzed, and then freeze-dried to obtain foamy methacryloyl chitosan.
[0016] Furthermore, step (3) is specifically as follows: adding methacryloyl chitosan to deionized water, and heating in a water bath at 60° C. to 70° C. for 0.5 h to 1 h to obtain a methacryloyl chitosan aqueous solution.
[0017] Furthermore, in step (4), 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone is added to the methacrylated chitosan aqueous solution, and stirred at room temperature for 10 min to 30 min to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, thereby obtaining a chitosan hydrogel precursor solution.
[0018] Furthermore, the main component of the super hydrophilic coating is polyacrylic acid.
[0019] Furthermore, in step (6), ultraviolet light with a wavelength of 365 nm is used for photocuring.
[0020] Furthermore, in step (6), Na2H 32 PO4 aqueous solution is phosphorus [ 32 P] sodium phosphate oral solution, and Na2H 32 The volume ratio of the PO4 aqueous solution to the chitosan hydrogel precursor solution is 1:10-100.
[0021] Furthermore, in step (6), Na2H 32 The radioactivity of PO4 aqueous solution is 0.2mCi / mL-2mCi / mL.
[0022] Compared with the prior art, this application has the following advantages and beneficial effects:
[0023] 1. Ordinary hydrogels are difficult to make thin due to the surface tension of water. If too little hydrogel solution is added to the mold, the solution is difficult to cover the mold. To cover the mold, more hydrogel solution needs to be added, which makes the hydrogel too thick. In the present application, the chitosan hydrogel precursor solution itself has a high viscosity. Combined with a polytetrafluoroethylene mold treated with a hydrophilic coating, a very small amount of chitosan hydrogel precursor solution can also cover the mold, thereby preparing an ultra-thin hydrogel applicator, thereby reducing the hydrogel material's own blocking of radiation and enhancing the efficacy of the applicator.
[0024] 2. In the present application, the solid content in the chitosan hydrogel precursor solution can be as low as 4%. A significant reduction in the solid content means that the blocking effect of the molecular chains in the hydrogel on radiation is also reduced, thereby further enhancing the therapeutic effect of the applicator.
[0025] 3. Chitosan needs to be acid-soluble. By acylating chitosan with methacrylic anhydride, water-soluble methacrylic chitosan is obtained. The water solubility of methacrylic chitosan also changes with the degree of acylation, making the preparation of chitosan hydrogel precursor solution more convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a physical photo of the sample of Example 1;
[0027] Figure 2 Schematic diagram of thickness measurement of the sample in Example 1;
[0028] Figure 3 This is a scanning electron microscope photograph of the surface of the hydrogel sample of Example 2;
[0029] Figure 4 is a scanning electron microscope photograph of a cross section of the hydrogel sample of Example 2;
[0030] Figure 5 The acylation degree statistics of samples with different methacrylic anhydride addition amounts are shown in FIG.
[0031] Figure 6 It is the solubility statistics of samples with different acylation degrees;
[0032] Figure 7 It is the statistical diagram of P element retention rate of samples with different nuclide concentrations;
[0033] Figure 8 Statistical diagram of unit activity dose rate for samples of different thicknesses. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be described clearly and completely in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0035] It should be noted that in the following examples, Na2H 32 PO4 aqueous solution is made from phosphorus from Atom High-Tech Co., Ltd. 32 P] acid sodium salt oral solution.
[0036] Example 1
[0037] In this embodiment, the load 32 The ultra-thin sheet chitosan hydrogel applicator of P is prepared in the following steps:
[0038] (1) 2 g of chitosan powder was added to 200 mL of water, and then 2 mL of acetic acid was added dropwise, and the mixture was placed in a 60° C. oil bath and stirred for 60 min to completely dissolve the chitosan powder, thereby obtaining a chitosan aqueous solution;
[0039] (2) adding methacrylic anhydride dropwise to the chitosan aqueous solution and reacting in a water bath at 60° C. for 6 h, and then adjusting the reaction solution to neutrality with a 10 mol / L sodium hydroxide solution, wherein the molar ratio of methacrylic anhydride to amino groups in chitosan is 5:1;
[0040] (3) The neutral reaction solution was poured into a dialysis bag and dialyzed in a beaker for 3 days, with the water changed 5 times a day; the solution was then freeze-dried for 72 hours. When the solution was freeze-dried into a foamy state, methacryloyl chitosan was prepared;
[0041] (4) adding 400 mg of methacryloyl chitosan to 10 mL of deionized water, and heating in a water bath at 60° C. for 1 h to completely dissolve the methacryloyl chitosan to obtain a methacryloyl chitosan aqueous solution;
[0042] (5) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacrylated chitosan aqueous solution, stirring at room temperature for 20 minutes to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and obtaining a chitosan hydrogel precursor solution; wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacrylated chitosan is 1:8;
[0043] (6) Take a polytetrafluoroethylene mold with a length of 50 mm, a width of 50 mm, and a height of 3 mm, apply a layer of super-hydrophilic coating on the inner surface of the mold, and air-dry it for 20 minutes; in this embodiment, the super-hydrophilic coating is a commercially available Paiqi nano ATF202 coating agent, the main component of which is polyacrylic acid; the super-hydrophilic coating can improve the hydrophilicity of the surface of the polytetrafluoroethylene mold and reduce its water contact angle;
[0044] (7) Na2H 32 PO4 aqueous solution and methacryloyl chitosan aqueous solution were added to the mold, stirred evenly, and then cured with ultraviolet light at a wavelength of 365 nm. 32 The radioactivity of the PO4 aqueous solution is 0.5 mCi / mL; the Na2H 32 The total volume of the PO4 aqueous solution and the methacryloyl chitosan aqueous solution should satisfy the following requirement: the value of the total volume divided by the bottom area of the mold is 0.5 mm2;
[0045] (8) Take out the solidified hydrogel and encapsulate it between two layers of transparent tape to obtain a loaded 32 Ultrathin sheet chitosan hydrogel applicator of P.
[0046] See also Figure 1 , which is a real photo of the sample of this embodiment; please refer to Figure 2 , which is a schematic diagram of thickness measurement of the sample of this embodiment, the thickness of the sample is 0.5 mm.
[0047] Example 2
[0048] In this embodiment, the load 32 The ultra-thin sheet chitosan hydrogel applicator of P is prepared in the following steps:
[0049] (1) 2.5 g of chitosan powder was added to 200 mL of water, and then 2 mL of acetic acid was added dropwise. The mixture was placed in a 60°C oil bath and stirred for 60 min to completely dissolve the chitosan to obtain a chitosan aqueous solution;
[0050] (2) adding methacrylic anhydride dropwise to the chitosan aqueous solution and reacting for 6 hours, and then adjusting the reaction solution to neutrality with a 10 mol / L sodium hydroxide solution, wherein the molar ratio of methacrylic anhydride to amino groups in chitosan is 7:1;
[0051] (3) The neutral reaction solution was poured into a dialysis bag and dialyzed in a beaker for 3 days, with the water changed 5 times a day; the solution was then freeze-dried for 72 hours. When the solution was freeze-dried into a foamy state, methacryloyl chitosan was prepared;
[0052] (4) adding 450 mg of methacryloyl chitosan to 10 mL of deionized water, and heating in a water bath at 60° C. for 1 h to completely dissolve the methacryloyl chitosan to obtain a methacryloyl chitosan aqueous solution;
[0053] (5) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacrylated chitosan aqueous solution, stirring at room temperature for 20 minutes to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and obtaining a chitosan hydrogel precursor solution; wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacrylated chitosan is 1:20;
[0054] (6) Take a polytetrafluoroethylene mold with a length of 50 mm, a width of 50 mm, and a height of 3 mm, apply a layer of super-hydrophilic coating on the inner surface of the mold, and air-dry it for 20 minutes; in this embodiment, the super-hydrophilic coating is a commercially available Paiqi nano ATF202 coating agent, the main component of which is polyacrylic acid; the super-hydrophilic coating can improve the hydrophilicity of the mold surface and reduce its water contact angle. ;
[0055] (7) Na2H 32 PO4 aqueous solution and methacryloyl chitosan aqueous solution were added to the mold, stirred evenly, and cured with ultraviolet light at a wavelength of 365 nm. 32 The radioactivity of the PO4 aqueous solution is 0.5 mCi / mL; the Na2H 32 The total volume of the PO4 aqueous solution and the methacryloyl chitosan aqueous solution should satisfy the following requirement: the value of the total volume divided by the bottom area of the mold is 0.5 mm.
[0056] The solidified hydrogel samples were taken out and the microscopic morphology of the hydrogel samples was observed using a desktop scanning electron microscope. The hydrogel samples were first freeze-dried, the cross-section was discarded, and then dried and gold-sprayed for observation. The obtained scanning electron microscope photos are shown in Figure 3-4 .in, Figure 3 is the surface of the hydrogel sample, Figure 4 is the cross section of the hydrogel sample. Figure 3-4It can be seen that the cross-linked network structure of the hydrogel can ensure that the hydrogel has good mechanical properties, and the evenly distributed dense pores can ensure 32 Uniform load of P.
[0057] Example 3
[0058] In this example, three groups of samples were prepared. The difference between each group of samples was only the molar ratio of methacrylic anhydride to the amino group in chitosan. The preparation steps were as follows:
[0059] (1) 3 g of chitosan powder was added to 200 mL of water, and then 2 mL of acetic acid was added dropwise. The mixture was placed in a 60°C oil bath and stirred for 60 min to completely dissolve the chitosan to obtain a chitosan aqueous solution;
[0060] (2) Methacrylic anhydride was added dropwise to the chitosan aqueous solution and reacted in a water bath at 55-65°C for 6 h. The reaction solution was then adjusted to neutral with a 10 mol / L sodium hydroxide solution. The molar ratios of methacrylic anhydride to amino groups in chitosan in the three groups of samples were 5:1, 10:1, and 15:1, respectively.
[0061] (3) The neutral reaction solution was poured into a dialysis bag and dialyzed in a beaker for 3 days, with the water changed 5 times a day; the solution was then freeze-dried for 72 hours. When the solution was freeze-dried into a foamy state, methacryloyl chitosan was prepared;
[0062] (4) taking 500 mg of methacryloyl chitosan and adding it to 10 mL of deionized water, heating it in a water bath at 60° C. for 1 h to completely dissolve the methacryloyl chitosan, thereby obtaining a methacryloyl chitosan aqueous solution;
[0063] (5) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacrylated chitosan aqueous solution, stirring at room temperature for 20 minutes to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and obtaining a chitosan hydrogel precursor solution; wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacrylated chitosan is 1:15;
[0064] (6) Take a polytetrafluoroethylene mold with a length of 50 mm, a width of 50 mm, and a height of 3 mm, apply a layer of super-hydrophilic coating on the inner surface of the mold, and air-dry it for 20 minutes; in this embodiment, the super-hydrophilic coating is a commercially available Paiqi nano ATF202 coating agent, the main component of which is polyacrylic acid; the super-hydrophilic coating can improve the hydrophilicity of the surface of the polytetrafluoroethylene mold and reduce its water contact angle;
[0065] (7) Na2H 32PO4 aqueous solution and methacryloyl chitosan aqueous solution were added to the mold, stirred evenly, and cured with ultraviolet light at a wavelength of 365 nm. 32 The radioactivity of the PO4 aqueous solution is 1 mCi / mL; the Na2H 32 The total volume of the PO4 aqueous solution and the methacryloyl chitosan aqueous solution should satisfy the following requirement: the value of the total volume divided by the bottom area of the mold is 0.5 mm.
[0066] (8) Take out the cured hydrogel sample.
[0067] 5 mg of each of the three groups of samples were taken to detect the acylation degree. The sample taken here was the methacrylic acylated chitosan prepared in step (3). The detection method was as follows: the sample was dissolved in 0.6 mL of D2O, added to the NMR tube with a syringe, and the NMR spectrum was analyzed using a NMR spectrometer. The degree of substitution of methacrylic anhydride, i.e., the degree of acylation, was calculated based on the NMR spectrum results. The results are shown in Figure 5 As shown, the abscissa represents the molar ratio of methacrylic anhydride to the amino group in chitosan. Figure 5 It can be seen that as the amount of methacrylic anhydride added increases, the degree of acylation also increases.
[0068] 100 mg of each of the three groups of samples were taken and the water solubility was determined by turbidity method: the sample was dissolved in 5 ml of deionized water, deionized water was slowly added to the solution, and the transmittance of the solution at 500 nm was tested using a UV-Vis spectrometer. The results are as follows: Figure 6 As shown, the abscissa represents the molar ratio of methacrylic anhydride to the amino group in chitosan. Figure 6 It can be seen that as the degree of acylation increases, the solubility concentration of methacrylic chitosan in aqueous solution also increases. This may be because after chitosan is acylated, the methacrylic anhydride grafted on the molecular weight reduces the intermolecular force of CS in chitosan, thereby improving its water solubility.
[0069] Example 4
[0070] In this example, 4 groups of samples were prepared. The difference between each group of samples was only in the radioactivity of the nuclide. The preparation steps were as follows:
[0071] (1) 3 g of chitosan powder was added to 200 mL of water, and then 2 mL of acetic acid was added dropwise. The mixture was placed in a 60°C oil bath and stirred for 60 min to completely dissolve the chitosan to obtain a chitosan aqueous solution;
[0072] (2) adding methacrylic anhydride dropwise to the chitosan aqueous solution and reacting in a water bath at 55-65° C. for 6 h, and then adjusting the reaction solution to neutrality with a 10 mol / L sodium hydroxide solution, wherein the molar ratio of methacrylic anhydride to amino groups in chitosan is 5:1;
[0073] (3) The neutral reaction solution was poured into a dialysis bag and dialyzed in a beaker for 3 days, with the water changed 5 times a day; the solution was then freeze-dried for 72 hours. When the solution was freeze-dried into a foamy state, methacryloyl chitosan was prepared;
[0074] (4) taking 500 mg of methacryloyl chitosan and adding it to 10 mL of deionized water, heating it in a water bath at 60° C. for 1 h to completely dissolve the methacryloyl chitosan, thereby obtaining a methacryloyl chitosan aqueous solution;
[0075] (5) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacrylated chitosan aqueous solution, stirring at room temperature for 20 minutes to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and obtaining a chitosan hydrogel precursor solution; wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacrylated chitosan is 1:15;
[0076] (6) Take a polytetrafluoroethylene mold with a length of 50 mm, a width of 50 mm, and a height of 3 mm, apply a layer of super-hydrophilic coating on the inner surface of the mold, and air-dry it for 20 minutes; in this embodiment, the super-hydrophilic coating is a commercially available Paiqi nano ATF202 coating agent, the main component of which is polyacrylic acid; the super-hydrophilic coating can improve the hydrophilicity of the surface of the polytetrafluoroethylene mold and reduce its water contact angle;
[0077] (7) Na2H 32 PO4 aqueous solution and methacryloyl chitosan aqueous solution were added to the mold, stirred evenly, and photocured with ultraviolet light of wavelength 365nm; the Na2H 32 The total volume of the PO4 aqueous solution and the methacryloyl chitosan aqueous solution should satisfy the following requirement: the value of the total volume divided by the bottom area of the mold is 0.5 mm. The radioactivity of the nuclides in the four groups of samples are 0.5 mCi / mL, 1 mCi / mL, and 2 mCi / mL, respectively.
[0078] ICP (inductively coupled plasma spectrometer) was used to quantitatively analyze the four groups of samples in this embodiment, and the 32 P content statistics, see Figure 7 , where the horizontal axis represents the radioactivity of the nuclide. Figure 7 It can be seen that the loss of P element in each group of samples after gelation is within 20%, proving that the utilization rate of nuclides is high during the preparation of the applicator.
[0079] Example 5
[0080] In this embodiment, three groups of samples were prepared. The difference between each group of samples was only in thickness. The preparation steps were as follows:
[0081] (1) 4 g of chitosan powder was added to 200 mL of water, and then 2 mL of acetic acid was added dropwise. The mixture was placed in a 60°C oil bath and stirred for 60 min to completely dissolve the chitosan to obtain a chitosan aqueous solution;
[0082] (2) adding methacrylic anhydride dropwise to the chitosan aqueous solution and reacting in a water bath at 55-65° C. for 6 h, and then adjusting the reaction solution to neutrality with a 10 mol / L sodium hydroxide solution, wherein the molar ratio of methacrylic anhydride to amino groups in chitosan is 16:1;
[0083] (3) The neutral reaction solution was poured into a dialysis bag and dialyzed in a beaker for 3 days, with the water changed 5 times a day; the solution was then freeze-dried for 72 hours. When the solution was freeze-dried into a foamy state, methacryloyl chitosan was prepared;
[0084] (4) taking 500 mg of methacryloyl chitosan and adding it to 10 mL of deionized water, heating it in a water bath at 60° C. for 1 h to completely dissolve the methacryloyl chitosan, thereby obtaining a methacryloyl chitosan aqueous solution;
[0085] (5) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacrylated chitosan aqueous solution, stirring at room temperature for 20 minutes to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, and obtaining a chitosan hydrogel precursor solution; wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacrylated chitosan is 1:16;
[0086] (6) Take a polytetrafluoroethylene mold with a length of 50 mm, a width of 50 mm, and a height of 3 mm, apply a layer of super-hydrophilic coating on the inner surface of the mold, and air-dry it for 20 minutes; in this embodiment, the super-hydrophilic coating is a commercially available Paiqi nano ATF202 coating agent, the main component of which is polyacrylic acid; the super-hydrophilic coating can improve the hydrophilicity of the surface of the polytetrafluoroethylene mold and reduce its water contact angle;
[0087] (7) Na2H 32 PO4 aqueous solution and methacryloyl chitosan aqueous solution were added to the mold, stirred evenly, and cured with ultraviolet light at a wavelength of 365 nm. 32 The radioactivity of PO4 aqueous solution was 0.35 mCi / mL; for the three groups of samples, the Na2H 32 The total volume of the PO4 aqueous solution and the methacryloyl chitosan aqueous solution respectively satisfies: the value of the total volume divided by the bottom area of the mold is 0.4 mm, 0.5 mm, and 1 mm. That is, the thickness of the three groups of samples is 0.4 mm, 0.5 mm, and 1 mm, respectively.
[0088] The hydrogel samples were taken out and the unit activity dose rate of samples with different thicknesses was calculated. The results are shown in Figure 8 ,from Figure 8 It can be seen that when the marked activity is 0.35mCi, the unit activity dose rate of the sample with a thickness of 1mm is reduced from 1101mGy / (h*mCi) to 1068mGy / (h*mCi) compared with the sample with a thickness of 0.4mm. This shows that the thickness of the hydrogel has a significant effect on the activity, and making the hydrogel in the applicator thinner can better play the role of the nuclide.
[0089] Note that the above are only preferred embodiments of the present application and the technical principles used. Those skilled in the art will understand that the present application is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the protection scope of the present application. Therefore, although the present application is described in more detail through the above embodiments, the present application is not limited to the above embodiments, and may also include more other equivalent embodiments without departing from the concept of the present application, all of which belong to the protection scope of the present application.
Claims
1. A load 32 The preparation method of an ultra-thin sheet chitosan hydrogel applicator of P is characterized by comprising: (1) Add 1 g to 2 g of chitosan per 100 mL of water to prepare a chitosan aqueous solution; (2) adding methacrylic anhydride dropwise to the chitosan aqueous solution to react to obtain methacrylic chitosan, wherein the molar ratio of methacrylic anhydride to amino groups in chitosan is 5-16:1; (3) adding 400 mg to 500 mg of methacryloyl chitosan per 10 mL of water to prepare a methacryloyl chitosan aqueous solution; (4) adding 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to the methacryloyl chitosan aqueous solution to obtain a chitosan hydrogel precursor solution, wherein the mass ratio of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone to methacryloyl chitosan is 1:8-20; (5) coating the inner wall of the polytetrafluoroethylene mold with a super-hydrophilic coating and allowing it to air dry naturally; (6) Na2H 32 PO4 aqueous solution and chitosan hydrogel precursor solution are added into the mold, stirred and then light-cured; (7) The cured hydrogel is taken out and packaged between two layers of transparent tape to obtain an ultra-thin chitosan hydrogel applicator.
2. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: Step (1) is specifically as follows: adding chitosan powder to water, then dropping acetic acid, placing in a 60°C-70°C oil bath and stirring for 30min-60min until the chitosan powder is completely dissolved; the amount of acetic acid used is: the volume of acetic acid is 1%-2% of the volume of water.
3. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: Step (2) is specifically as follows: methacrylic anhydride is added dropwise to the chitosan aqueous solution, and the mixture is reacted in a water bath at 55°C-65°C for 6h-8h, the reaction solution is then adjusted to neutral, the neutral reaction solution is dialyzed, and then freeze-dried to obtain foamy methacryloyl chitosan.
4. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: Step (3) is specifically as follows: adding methacryloyl chitosan to deionized water, and heating in a water bath at 60° C. to 70° C. for 0.5 h to 1 h to obtain a methacryloyl chitosan aqueous solution.
5. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: In step (4), 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone is added to the methacrylylated chitosan aqueous solution, and stirred at room temperature for 10 min to 30 min to dissolve the 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, thereby obtaining a chitosan hydrogel precursor solution.
6. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: The main component of the super hydrophilic coating is polyacrylic acid.
7. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: In step (6), ultraviolet light with a wavelength of 365 nm is used for photocuring.
8. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: In step (6), Na2H 32 PO4 aqueous solution is phosphorus [ 32 P] sodium phosphate oral solution, and Na2H 32 The volume ratio of the PO4 aqueous solution to the chitosan hydrogel precursor solution is 1:10-100.
9. The method for preparing the ultra-thin sheet chitosan hydrogel applicator according to claim 1, characterized in that: In step (6), Na2H 32 The radioactivity of PO4 aqueous solution is 0.2mCi / mL-2mCi / mL.
Citation Information
Patent Citations
Methacryloylated chitosan hydrogel microneedle patch as well as preparation method and application thereof
CN115671528A
Multifunctional injectable light-cured composite hydrogel and preparation method thereof
CN115919747A
Coating process of hydrophilic silicone hydrogel corneal contact lens
CN116554719A
Preparation method of PVA-based 32P radioactive therapy hydrogel applicator
CN116983464A
Flexible radioactive gel formed by ultraviolet curing
CN117547624A
Cited By
Ultrathin radioactive application for skin cancer treatment and preparation method thereof
CN120983667A
An ultrathin radioactive patch for skin cancer treatment and a preparation method thereof
CN120983667B